A weighted limit theorem for periodic Hurwitz zeta-function - Lukašonok, Oleg (Lietuvos matematikos rinkinys, 2012)
In the paper, a weighted limit theorem for weakly convergent probability measures on the complex plane for the periodic Hurwitz zeta function is obtained.
Keywords: periodic Hurwitz zeta function; probability measure; weak convergence